Awaiting discovery: How biases in faunistic surveys hinder conservation in mountain protected areas—A case study from Romania’s oldest national park - Dan Cogălniceanu; Dorel Ruşti; Marius Skolka; Florina Stănescu; Sabina E. Vlad; Teodora L. Tănase; Laurenţiu Rozylowicz (PLoS ONE, 2025)
It is virtually impossible to compile a complete list of species and map their distributions in any protected area; nevertheless, a near complete inventory is vital for an adequate management plan. We use Retezat National Park (Romania) as a case study to assess the bias in faunistic inventories over the past 70 years. Retezat National Park is one of the most studied in Eastern Europe since it shelters some of the last patches of virgin old-growth forest in Europe. We reviewed the scientific literature published since the early 1900s dealing with faunistic surveys and retrieved the occurrence records available on GBIF for the study area. We identified a total of 4374 animal species belonging to 2113 genera, 494 families, 99 orders, 23 classes, and nine phyla. The number of publications started to accumulate after 1979, when the park became a Biosphere Reserve, reached a peak in the early 2000 and severely decreased during the last decade, highlighting a decline in the researchers’ interest in faunistic surveys and, possibly, a delay between data collection and their publication. GBIF-mediated data made a small contribution, most records (60%) being collected in 2019. The bias analyses included only the distribution records available in the scientific literature, since they were already validated through peer-review. The number of publications and background of experts involved influenced the taxonomic coverage and inventory completeness. We found a strong spatial bias in terms of inventory coverage, with diversity hotspots located near roads and research facilities. Our study provides a roadmap for cost-effective future faunistic studies by prioritizing conservation efforts towards the most understudied areas and taxa within the park.